2015
DOI: 10.1136/jnnp-2014-309452
|View full text |Cite
|
Sign up to set email alerts
|

Lateralising value of experiential hallucinations in temporal lobe epilepsy

Abstract: These results suggest a lateralising value for experiential hallucinations to the left temporal lobe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…For the display of the seizure onset zone in patients with DV and EH please refer to the original work by Heydrich et al…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the display of the seizure onset zone in patients with DV and EH please refer to the original work by Heydrich et al…”
Section: Resultsmentioning
confidence: 99%
“…altered perception of one’s surroundings that is experienced as strange or unreal) as part of their habitual seizure semiology . Moreover, patients reporting déjà vu (DV) or experiential hallucinations (EH) were selected from the same population as an additional control group (see ). Patients were only included if they could be unequivocally assigned to one of the above mentioned four groups according to their semiology.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gupta et al (1983) found that right hemispheric EEG abnormalities were more likely in patients with psychic or autonomic auras. Heydrich et al (2015) suggest a lateralising value for experiential hallucinations to the left temporal lobe.…”
Section: Heinz Gregor Wiesermentioning
confidence: 96%